2018
DOI: 10.3892/mmr.2018.8776
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast prevents renal interstitial fibrosis by blocking mast cell infiltration in a rat model of diabetic kidney disease

Abstract: Renal interstitial fibrosis is a final pathway that is observed in various types of kidney diseases, including diabetic kidney disease (DKD). The present study investigated the effect of tranilast on renal interstitial fibrosis and the association between its role and mast cell infiltration in a rat model of DKD. A total of 30 healthy 6‑week‑old male Sprague‑Dawley rats were randomly divided into the following four groups: Normal control group; DKD model group; low‑dose tranilast group (200 mg/kg/day); and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…PSC is characterized by hepatic fibrosis and our current study supports our previous work demonstrating that blocking MC infiltration and degranulation decreases liver fibrosis and HSC activation [11,14,15,17,18]. To support this, it has been shown that the SCF/c-Kit interaction promotes renal interstitial fibrosis [30]. Similar to our current findings, the authors found that, in a diabetic kidney disease model, the expression of fibronectin and collagen type-1a increases in diseased rats compared to normal and this was associated with increased SCF and c-Kit gene expression [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PSC is characterized by hepatic fibrosis and our current study supports our previous work demonstrating that blocking MC infiltration and degranulation decreases liver fibrosis and HSC activation [11,14,15,17,18]. To support this, it has been shown that the SCF/c-Kit interaction promotes renal interstitial fibrosis [30]. Similar to our current findings, the authors found that, in a diabetic kidney disease model, the expression of fibronectin and collagen type-1a increases in diseased rats compared to normal and this was associated with increased SCF and c-Kit gene expression [30].…”
Section: Discussionsupporting
confidence: 89%
“…To support this, it has been shown that the SCF/c-Kit interaction promotes renal interstitial fibrosis [30]. Similar to our current findings, the authors found that, in a diabetic kidney disease model, the expression of fibronectin and collagen type-1a increases in diseased rats compared to normal and this was associated with increased SCF and c-Kit gene expression [30]. Additionally, following 70% partial hepatectomy, SCF levels increase over time and peak at 7 days [16].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of B cells in the kidney can promote monocyte/macrophage recruitment by the secretion of CCL2, thus aggravating renal fibrosis. NK cells and C3aR + cells are also positively correlated with TIF, but the mechanisms involved remain unclear 105 , 106 .…”
Section: How Do Tecs Interact With Other Cell Types In the Interstitimentioning
confidence: 99%
“…The release of such mediators from MCs may contribute to renal diseases and renal interstitial fibrosis and cause extracellular matrix (ECM) accumulation [53,54]. A recent study indicated that MC infiltration might promote renal interstitial fibrosis via the stem cell factor (SCF)/c-KIT signaling pathway, which can be inhibited by an antiallergic drug such as tranilast [55]. Another pathway in which MCs contribute to the pathogenesis of diabetic nephropathies might involve the renin-angiotensin system (RAS).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%